Quantum Computing for Logistics and Supply Chain Optimization - Carlos Pérez; Ana Rodríguez; Luis Hernández (Journal of Tecnologia Quantica, 2024)
The background of this research is related to the challenges faced by the logistics and supply chain industry in optimizing the process of planning shipping routes and managing operational costs. The application of quantum computing technology offers the potential to solve complex problems that are difficult to solve with conventional methods. The purpose of this study is to evaluate the effectiveness of quantum computing in logistics and supply chain optimization by reducing delivery time and operational costs. This research method involves the use of secondary data from three major logistics companies and the application of quantum computing-based optimization algorithms to analyze their influence on operational efficiency. The results show that the application of quantum computing can reduce average delivery time by 10% and operational costs by up to 10%, with a significant increase in customer satisfaction. The conclusion of this study confirms that quantum computing technology has the potential to bring about major changes in the logistics and supply chain industry by improving efficiency and reducing operational costs. Further research is needed to develop more specific algorithms and test the application of these technologies on a larger scale.